DETERMINATION OF VANADIUM IN VEGETABLE MATTER BY FLAME ATOMIC-ABSORPTION SPECTROMETRY - GUCER, S; YAMAN, M (Royal Soc Chemistry, 1992)
A method is described for the preconcentration of trace amounts of vanadium(v) from biological samples and its determination by flame atomic absorption spectrometry. It was found that the optimum acidity is in the pH range 2.9-4.9. An increase in the interferences from Al, Mg and Ca is observed. Elimination of these problems was achieved by adding an enrichment step to the analytical scheme. Linear calibration was obtained over the concentration range 10-120 ppb. The relative standard deviation was found to be 3% for a vanadium concentration of 100 ppb. The proposed enrichment method was applied to the determination of vanadium in foods and plants. The preconcentration system enables a 300-fold enrichment of vanadium(v) to be achieved, and therefore its determination at ppb levels. The proposed method tolerates the presence of a large number of cations that are usually found with vanadium in plant and animal tissues.
27TH INTERNATIONAL COLLOQUIUM ON SPECTROSCOPY ( 27TH CSI ) -- JUN 09-14, 1991 -- BERGEN, NORWAY
Keywords: VANADIUM(V) DETERMINATION; PRECONCENTRATION ON ACTIVATED CARBON; 8-HYDROXYQUINOLINE; ATOMIC ABSORPTION SPECTROMETRY; VEGETABLE MATTER